Rigid polyurethane foams derived from cork liquefied at atmospheric pressure - Gama, Nuno V.
The aim of this study was to evaluate the possibility of using polyols derived from liquefied cork in the production of novel bio-based polyurethane foams (PUFs). For that purpose, different liquefaction conditions were used at atmospheric pressure and moderate temperature where poly(ethylene glycol) and glycerol were used as solvents and sulfuric acid as catalyst. The ensuing polyols were used to produce foams which were characterized using structural, morphological, thermal and mechanical analyses to demonstrate that liquefaction conditions play a crucial role in the properties of the foams. The resulting foams exhibited the typical cellular structure of PUFs with low densities (57.4-70.7 kgm(-3)) and low thermal conductivities (0.038-0.040 Wm(-1)K(-1)). However, the mechanical properties differed significantly depending on the liquefaction conditions. The best stress-strain results were obtained for PUFs prepared using the polyol with lowest I-OH and water content (Young's modulus of 475.0 kPa, compressive stress (sigma(10%)) of 34.6 kPa and toughness of 7397.1 Jm(-3)). This PUF was thermally stable up to 200 degrees C and presented a glass transition temperature of around 27 degrees C. The results obtained demonstrate that these polyols from liquefied cork yield PUFs that are adequate materials for insulation applications. (c) 2014 Society of Chemical Industry